Analisis Fasilitas Dan Kegiatan Pembelajaran Siswa Di SLB Negeri Keleyan - Ifa Haryemi; Nova Estu Harsiwi (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research is a type of qualitative descriptive research. The analysis used is the analysis of facilities and student learning activities at the Keleyan State SLB. This research was conducted at Keleyan State SLB, Kec. Socah, Bangkalan Regency, East Java. The purpose of this study was to find out the facilities and learning activities in the Keleyan State SLB. The participants in this study were school principals, teachers of grades I, V and Keleyan State SLB students. Data collection techniques used in this study are observation, interviews, and documentation. The instruments used in this study were observation sheets and interview sheets. The results showed that the facilities provided to support student learning were adequate. Meanwhile, the learning activities carried out include; 1) Making Batik Patterns; 2) Literacy Activities; 3) Plastic Waste Recycling; 4) Dancing and Singing Activities; 5) Swimming Activities; 6) Commemorating the Big Day; 7) handicrafts; 8) PSP Workshop; 9) Outing Class; 10) Scouts; 11) Cooking Class; 12) and Healthy Friday.